HFE gene polymorphisms in Malays - Jatta, Francis (2020)
Variations in haemochromatosis gene (HFE) have been reported to inhibit the role of hepcidin, resulting in an autosomal genetic disorder called hereditary haemochromatosis (HH). These genetic variations include C282Y, H63D, and S65C which have been largely studied in Europeans and none for the Malaysian population. The aim of this study is to evaluate variations within the HFE gene in Malays. A total of 35 blood samples were collected and genotyped for C282Y, H63D, and S65C using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The findings of the study showed that the frequency distribution of heterozygous H63D (5.71%) was twice higher than those heterozygous for S65C (2.86%). However, no Malay individuals were homozygous or heterozygous for C282Y. Therefore, risk for HH in Malays is low as compared with Europeans which have high frequencies of C282Y, H63D, and S65C alleles and genotypes. Future study should include other population groups in Malaysia for better elucidation of population structure and risk for developing HH in the country.